AN ANALYSIS OF MASCULINITY IN BTS BOY BAND MUSIC VIDEOS - Hana Listia Firdah; Angga Maulana; Senny S Alwasilah (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
The massive popularity of K-Pop currently regards as one of the world's most popular. As a result, the researcher was drawn to the Bangtan Boys (BTS) music videos entitled We Are Bulletproof Pt.2 and Boy With Luv (feat. Halsey). This study aims to find out what kind of masculinity BTS Boy Band built and how they portrayed their masculinity in their music videos. The writer also used the qualitative descriptive based on Roland Barthes' semiotic theory as a sign system separated into denotation and connotation, which builds a myth to obtain the meaning. The results found that the type of masculinity represented by the BTS boyband is metrosexual, seonbi, and bishonen. They have portrayed their masculinity from fashion usage that crosses gender boundaries, expression, and gestures that they represent in the music videos. BTS has a significant role in society as a public figure, especially for the younger generation who love and understand themselves more. If the man himself has femininity and masculinity, there is nothing wrong. BTS has redefined masculinity in many ways, and the most obvious is how they present themselves physically. They portray how the freedom and flexibility to wear whatever they want regardless of gender. BTS also teaches men that it does not become harmful for men to admit that they are vulnerable. It is all right to be clumsy, and nobody will judge anything about it. Loving ourselves is more important than following popular standards in society (which is not necessarily good for one's mental health).